The role of thermal physiology in recent declines of birds in a biodiversity hotspot. (13th November 2015) - Milne, Robyn; Cunningham, Susan J.; Lee, Alan T. K.; Smit, Ben
Abstract : We integrated population, climate, and physiological data to investigate Fynbos birds' vulnerability to recent climate change. Species occupying cool ranges with warming trends showed greatest declines. However, physiological thermal thresholds varied and, with the exception of Cape Rockjumper, were not clearly the cause of decline in most species. Abstract : We investigated whether observed avian range contractions and population declines in the Fynbos biome of South Africa were mechanistically linked to recent climate warming. We aimed to determine whether there were correlations between preferred temperature envelope, or changes in temperature within species' ranges, and recent changes in range and population size, for 12 Fynbos-resident bird species, including six that are endemic to the biome. We then measured the physiological responses of each species at air temperatures ranging from 24 to 42°C to determine whether physiological thermal thresholds could provide a mechanistic explanation for observed population trends. Our data show that Fynbos-endemic species occupying the coolest regions experienced the greatest recent reductions in range and population size (>30% range reduction between 1991 and the present). In addition, species experiencing the largest increases in air temperature within their ranges showed the greatest declines. However, evidence for a physiological mechanistic link between warming and population declines was equivocal, with only the larger species showing low thermal thresholds for their body mass, compared with other birds globally. In addition, some species appear more vulnerable than others to air temperatures in their ranges above physiological thermal thresholds. Of these, the high-altitude specialist Cape rockjumper ( Chaetops frenatus ) seems most at risk from climate warming. This species showed: (i) the lowest threshold for increasing evaporative water loss at high temperatures; and (ii) population declines specifically in those regions of its range recording significant warming trends. Our findings suggest that caution must be taken when attributing causality explicitly to thermal stress, even when population trends are clearly correlated with rates of warming. Studies explicitly investigating the mechanisms underlying such correlations will be key to appropriate conservation planning.